Strategi Supervisi Akademik dengan Choacing Alur Tirta di UPT SMP Negeri 29 Gresik dan UPT SMP Negeri 33 Gresik - Mochamad Choirudin; Andi Kristanto; Mohammad Syahidul Haq; Amrozi Khamidi; Muhammad Nur Salim (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to gain a deeper understanding of the implementation of academic supervision using the TIRTA coaching model in improving teacher professionalism at UPT SMP Negeri 29 Gresik and UPT SMP Negeri 33 Gresik. The research method used is descriptive qualitative, which focuses on collecting data obtained through observation, interviews, and document analysis. This study was conducted in January 2025, where teachers had planned their annual performance in the GTK (Portal Merdeka Mengajar) room. School supervisors and subject teachers acted as resource persons in this study. The results of the study indicate that academic supervision using the TIRTA model improves teachers' abilities in planning, implementing, and evaluating learning. The supervision process consists of three main stages, namely pre-observation, observation, and post-observation, each of which makes a significant contribution to improving the quality of learning. During the supervision process, school supervisors use a coaching approach that builds trust, provides constructive feedback, and supports teacher professional development. This study reveals several challenges in implementing supervision, such as the lack of experience of school principals in using the supervision model and teacher awareness of the importance of academic supervision. In conclusion, this study shows that the implementation of academic supervision of the TIRTA flow can bring positive changes in the quality of learning in schools, as well as improve working relationships between principals, supervisors, and teachers.  Keywords: Academic Supervision, Coaching, Teacher Professionalism, Tirta Flow